There is no F in APC: Using physiological fluoride-free solutions for high throughput automated patch clamp experiments - Rapedius, Markus; Obergrussberger, Alison; Humphries, Edward S. A.; Scholz, Stephanie; Rinke-Weiss, Ilka; Goetze, Tom A.; Brinkwirth, Nina; Rotordam, Maria Giustina; Strassmaier, Tim; Randolph, Aaron; Friis, Søren; Liutkute, Aiste; et al. (Frontiers in Molecular Neuroscience, 2022)
Fluoride has been used in the internal recording solution for manual and automated patch clamp experiments for decades because it helps to improve the seal resistance and promotes longer lasting recordings. In manual patch clamp, fluoride has been used to record voltage-gated Na (NaV) channels where seal resistance and access resistance are critical for good voltage control. In automated patch clamp, suction is applied from underneath the patch clamp chip to attract a cell to the hole and obtain a good seal. Since the patch clamp aperture cannot be moved to improve the seal like the patch clamp pipette in manual patch clamp, automated patch clamp manufacturers use internal fluoride to improve the success rate for obtaining GΩ seals. However, internal fluoride can affect voltage-dependence of activation and inactivation, as well as affecting internal second messenger systems and therefore, it is desirable to have the option to perform experiments using physiological, fluoride-free internal solution. We have developed an approach for high throughput fluoride-free recordings on a 384-well based automated patch clamp system with success rates >40% for GΩ seals. We demonstrate this method using hERG expressed in HEK cells, as well as NaV1.5, NaV1.7, and KCa3.1 expressed in CHO cells. We describe the advantages and disadvantages of using fluoride and provide examples of where fluoride can be used, where caution should be exerted and where fluoride-free solutions provide an advantage over fluoride-containing solutions.